Vaccination coverage and out-of-sequence vaccinations in rural Guinea-Bissau: an observational cohort study - Hornshøj, Linda (BMJ Publishing Group, 2012)
OBJECTIVE: The WHO aims for 90% coverage of the Expanded Program on Immunization (EPI), which in Guinea-Bissau included BCG vaccine at birth, three doses of diphtheria−tetanus−pertussis vaccine (DTP) and oral polio vaccine (OPV) at 6, 10 and 14 weeks and measles vaccine (MV) at 9 months when this study was conducted. The WHO assesses coverage by 12 months of age. The sequence of vaccines may have an effect on child mortality, but is not considered in official statistics or assessments of programme performance. We assessed vaccination coverage and frequency of out-of-sequence vaccinations by 12 and 24 months of age. DESIGN: Observational cohort study. SETTING AND PARTICIPANTS: The Bandim Health Project's (BHP) rural Health and Demographic Surveillance site covers 258 randomly selected villages in all regions of Guinea-Bissau. Villages are visited biannually and vaccination cards inspected to ascertain vaccination status. Between 2003 and 2009 vaccination status by 12 months of age was assessed for 5806 children aged 12–23 months; vaccination status by 24 months of age was assessed for 3792 children aged 24–35 months. OUTCOME MEASURES: Coverage of EPI vaccinations and frequency of out-of-sequence vaccinations. RESULTS: Half of 12-month-old children and 65% of 24-month-old children had completed all EPI vaccinations. Many children received vaccines out of sequence: by 12 months of age 54% of BCG-vaccinated children had received DTP with or before BCG and 28% of measles-vaccinated children had received DTP with or after MV. By 24 months of age the proportion of out-of-sequence vaccinations was 58% and 35%, respectively, for BCG and MV. CONCLUSIONS: In rural Guinea-Bissau vaccination coverage by 12 months of age was low, but continued to increase beyond 12 months of age. More than half of all children received vaccinations out of sequence. This highlights the need to improve vaccination services.